Bioinformatics analysis of duck PPARα gene structure and function - MA Yun; WANG Yun-yun; ZHANG Xiao-ting; LI Fen; WANG Qi-zhao; WANG Xin-zhuang (浙江大学学报. 农业与生命科学版)
Protein structures, physical and chemical properties, and their functional domain structures encoded by duck peroxisome proliferators-activated receptors-α (PPARα) gene were analyzed using bioinformatics method. Sequencing and bioinformatics analysis showed that the duck PPARα cDNA sequence was 1 430 base pairs long with an open reading frame (ORF) containing 1 407 nucleotides encoding a protein of 468 amino acids. The multiple sequence alignment showed that coding nucleotide sequences of the obtained duck PPARα gene had 96%, 92%, 79%, 77%, 78% homology with the corresponding chicken, Taeniopygia guttata, human, bovine and Equus caballus, respectively, and the deduced amino acid sequences had 98%, 97%, 89%, 89%, 88% identity with the corresponding species, respectively. Phylogenetic tree analysis of the amino acid sequences of duck PPAR α and other PPARα proteins in human and other animals showed that, among all the species mentioned above, the nearest relationship existed between duck and chicken. Further analysis on the structure and function of the duck PPARα protein showed that there were much more α helix than other secondary structure in the duck PPARα protein, besides, it had a short nuclear localization signal (KKNRNKC), so that it could enter into nucleus. Moreover, a DNA binding domain which was composed of two C4-type zinc fingers and a ligand binding domain was found in the PPARα protein.